Effect of Mannose Receptor (MR)-binding polymers on human macrophages - de Medeiros Costa, Diego (2019)
Mannose receptor (MR) is an endocytic lectin receptor with the capacity to bind sugars and collagen through its different domains. This receptor is mainly found in macrophages and dendritic cells and is important in pathogen recognition, cell activation, antigen presentation, control of homeostasis, and cell adhesion. It has been under study over the past decades and became a target in drug development. With the intention to modulate its function, our group had developed a library of glycopolymers, with different sugar moieties conjugated as pendant groups and with different lengths able to bind to different domains of MR. Our previous studies showed that glycopolymers with SO4-3-Gal sugar moieties were able to bind to mouse macrophages through the CR domain of MR in a pH-independent manner leading to decreased MR expression on the cell surface and inhibiting the collagen uptake activity in these cells. Its mechanism of action is thought to be by trapping of MR in the form of a complex of glycopolymer-MR in the endosome. The hypotheses of this project are that SO4-3-Gal glycopolymers could be recognised by human MR and modulate MR-function in human myeloid cells. Therefore, the aims of this project are: 1) Investigate the recognition of SO4-3-Gal glycopolymers by the CR domain of human MR and by human myeloid cells; 2) Investigate the effect of glycopolymers on MR function in human myeloid cells; and 3) Investigate the effect of glycopolymers on MR distribution within human myeloid cells. The results showed that SO4-3-Gal glycopolymers are recognized by human macrophages and its binding is dependent on polymer concentration and temperature of incubation. These polymers inhibited MR surface expression, as well as, decreased collagen uptake by human monocyte-derived macrophages. Macrophages were affected by these polymers and presented less MHCII molecules on its surface in response to IFN-γ and produced less kynurenine in response to IFN-γ and LPS. However, it was not possible to confirm trapping of MR in the endosome. It was also found that IFN-γ stimulation in human macrophages does not lead to decreased MR expression, as it is expected in mice. The results achieved in this thesis with the SO4-3-Gal GPs are novel in relation to MR surface blocking, collagen uptake inhibition and IDO inhibition in human macrophages. It adds to the current targeting strategies of MR. It also opens the possibility to explore cellular activities that could be affected by carbohydrate-based targeting approaches like modulation of cell growth, cell migration or other effector functions such as cytokine release.